Changes in spectroscopic signatures in soluble microbial products of activated sludge under different osmotic stress conditions. (May 2018) - Maqbool, Tahir; Cho, Jinwoo; Hur, Jin
Graphical abstract: Highlights: Dynamics of SMP composition at different salinity is well reflected in fluorescence. Tryptophan-like C1 was higher in SMP at elevated salinity and substrate depletion. C1/C2 ratio can be a good SMP signature for microbial response to salinity. 2D-COS revealed opposite sequences in fluorescence changes at different salinity. Abstract: Spectroscopic techniques were used to examine the subtle changes in soluble microbial products (SMP) of batch activated sludge bioreactors working at different salinities (i.e., 0%, 1%, 3%, and 5% NaCl). The changes in different fluorescent constituent were tracked by excitation-emission matrix combined with parallel factor analysis (EEM-PARAFAC), and the sequential production was further identified by two-dimensional correlation spectroscopy (2D-COS). Greater enrichment of tryptophan-like component and large-sized biopolymer were found in SMP for higher saline bioreactors, suggesting the SMP sources from bound extracellular polymeric substances and excreted intercellular constituents. 2D-COS revealed the opposite sequences of the fluorescence changes in SMP between the low and the high saline bioreactors, following the order of "tyrosine-like > tryptophan-like > humic-like fluorescence" for the latter. This study clarified the dominant mechanisms involved in SMP formation during elevating salinity, which were well supported by the changes in SMP spectroscopic features, microbial activity, and organic degradation rates.